Combining series of multi-source high spatial resolution remote sensing datasets for the detection of shoreline displacement rates and the effectiveness of coastal zone protection measures - Tsokos, A.; Kotsi, E.; Petrakis, S.; Vassilakis, Emm (Journal of Coastal Conservation, 2018)
The long-term change of the shoreline location is a phenomenon, which is highly factored in the design of construction projects along the coastal zone. Especially, beach erosion is characterized as one of the major problems at coastal areas and it is of high importance as a quite significant percentage of social development is concentrated in a relatively narrow zone not far from the waterfront. This study presents a methodology that aims to quantify the shoreline displacement rate by involving the processing of different types of remote sensing datasets such as aerial photographs, satellite images and unmanned aerial system data coupled with in-situ observations and measurements. Several photogrammetric techniques were used in order to orthorectify and homogenize a time series of remotely sensed data acquired from 1945 to 2017, representing a rapidly relocating coastal zone at the southern part of Corinth Gulf (Greece), as a case study. All images were digitally processed and optically optimized in order to produce a highly accurate representation of the shoreline at the time period of each acquisition. The data were imported in a Geographic Information System platform, where they were subjected to comparison and geostatistical analysis. High erosion rates were calculated, reaching the order of 0.18 m/year on average whilst extreme rates of 0.70 m/year were also observed in specific locations leading to the segmentation of the coastal zone according to its vulnerability and consequently the risk for further development as well as the effectiveness of measures already taken by the authorities.